Hubungan Verbal Bullying dengan Rasa Percaya Diri dan Motivasi Belajar Siswa di Lingkungan Inklusif - Anita Fadila Putri (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The prevalence of verbal bullying in inclusive educational settings remains a critical challenge that impacts students' psychological and academic development. This study aims to examine the relationship between verbal bullying, self-confidence, and learning motivation among students in inclusive primary and secondary schools through a sociolinguistic lens. The research employs a qualitative descriptive method with a literature review approach. Data were collected through the systematic searching and analysis of academic documents, including scientific journals, books, and proceedings from databases such as Google Scholar. The data analysis used thematic content analysis to identify patterns, concepts, and key findings regarding the impact of linguistic interaction on student behavior. The results indicate that sociolinguistic-based interventions, such as authentic discourse analysis, role-playing simulations, and discussions on language variation, can be effectively implemented to mitigate bullying. These approaches have a positive impact on students' understanding of language registers, politeness, and context-appropriate communication. Furthermore, there is a significant improvement in students' pragmatic and sociocultural competence, which directly correlates with increased self-confidence and learning motivation. This study concludes that sociolinguistic serves as a vital bridge between linguistic knowledge and practical communication skills. Integrating this approach is essential for preparing students for real-world social interactions while fostering a supportive and inclusive learning environment.